Nearly Zero Energy Standard for Non-Residential Buildings with high Energy Demands—An Empirical Case Study Using the State-Related Properties of BAVARIA - Michael Keltsch; Werner Lang; Thomas Auer (Buildings, 2017)
The Energy Performance of Buildings Directive (EPBD) 2010 calls for the Nearly Zero Energy Building (nZEB) Standard for new buildings from 2021 onwards: Buildings using “almost no energy” are powered by renewable sources or by the energy produced by the building itself. For residential buildings, this ambitious new standard has already been reached. But for other building types, this goal is still far away. The potential of these buildings to meet a nZEB Standard was investigated by analyzing ten case studies, representing non-residential buildings with different uses. The analysis shows that the primary characteristics common to critical building types are a dense building context with a very high degree of technical installation (such as hospital, research, and laboratory buildings). The large primary energy demand of these types of buildings cannot be compensated by building- and property-related energy generation, including off-site renewables. If the future nZEB Standard were to be defined with lower requirements because of this, the state-related properties of Bavaria suggest that the real potential energy savings available in at least 85% of all new buildings would be insufficiently exploited. Therefore, it would be more useful to individualize the legal energy verification process for new buildings, to distinguish critical building types such as laboratories and hospitals from the other building types.